Aortopathy - Niwa, Koichiro; Kaemmerer, Harald; SpringerLink (Online service) (Tokyo : Springer Japan : Imprint: Springer, 2017)
This is the first textbook to focus on Aortopathy, a new clinical concept for a form of vasculopathy. The first section of the book starts from discussing general concept and history of Aortopathy, and then deals with its pathophysiology, manifestation, intrinsic factor, clinical implication, management and prevention. The second part closely looks at various disorders of the Aortopathy such as bicuspid aortic valve and coarctation of aorta. The book editors have published a lot of works on the topic and have been collecting relating data in the field of congenital heart disease for the past 20 years, thus present the book with confidence. The topic - an association of aortic pathophysiological abnormality, aortic dilation and aorto-left ventricular interaction - is getting more and more attention among cardiovascular physicians. This is the first book to refer for cardiologists, pediatric cardiologists, surgeons, ACHD specialists, etc. to acquire thorough knowledge on Aortopathy. .
Part I Overview -- 1 History of Aortopathy -- 2 Pathological Background -- 3 Physiological Background -- 4 Aortopathies: Clinical Manifestation -- 5 Genetics of Marfan Syndrome, Related Disorders and Bicuspid Aortic Valve -- Part II Diagnosis and Management -- 6 Imaging in Aortopathy: Echo, CT and MRI -- 7 Pulse Wave Velocity and Augmentation Index -- 8 Comprehensive Assessment of Aortopathy Using Catheterization -- 9 Aortopathy in Pregnancy and Delivery -- 10 Medications -- 11 Clinical Diagnosis and Surgical Therapy of the Ascending Aorta and the Aortic Arch -- 12 Surgery (Bentall, Valve Sparing, Ross Procedure etc.) -- 13 Stenting -- Part III Various Disorders That Represent Aortopathy -- 14 The Marfan Syndrome.-15 Bicuspid aortic valve -- 16 Aortic Coarctation.-17 Tetralogy of Fallot and pulmonary atresia with ventricular septal defect -- 18 Hypoplastic Left Heart Syndrome -- 19 Aortopathy in Transposition of the Great Arteries after Arterial Switch Operation -- 20 Aortopathy in Patients after the Fontan Operation -- 21 Future Research Project in Aortopathy.
Keywords: Medicine; Cardiology; Pediatrics; Cardiac surgery; Medicine & Public Health; Cardiology; Pediatrics; Cardiac surgery